The Use of the Arisan Card Method in Economics Learning - Aplonia Lau, Elfreda (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
Education is a conscious effort to realize something of cultural inheritance from one generation to another. Thus the importance of education in an effort to eradicate ignorance and fight poverty. Through intense economic education in the family environment, one can form economic human beings (homo economicus) who are productive and economical in the use of money and other resources. One of the important subjects in school is economics. The learning method uses the social gathering card. The social gathering card is one of cooperative learning, where students work together in groups to discuss the suitability of the answers to each question that comes out of a glass that has been shaken by the teacher. The type of research used is a quantitative descriptive approach which aims to find out how active students are using the social gathering card method in economics learning. The results of the analysis in this study indicate that there are positive results for the use of the arisan type card method for student learning in economics subjects. The average student learning activity is 79.78 in the